Swahili translation and cultural adaptation of the National Institutes of Health Stroke Scale - Waweru, Peter; Gatimu, Samwel Maina; Yulu, Elijah; Kibet, Stella; Ndiema, Dalphine; Mang'ombe, Adam; Matuja, Sarah Shali; Paul, Innocent Kitandu; Basinda, Matilda K.; Berling, Sospeter; Xavier, Gladness; Manakhe, Nassiuma; et al. (Journal of clinical neuroscience, 2025)
BACKGROUND: The severity of early neurologic deficits after stroke is the single most important predictor of post-stroke outcomes. Of all stroke severity scales, the National Institutes of Health Stroke Scale (NIHSS) is the most widely used. Despite being freely accessible, however, this tool remains underutilized in sub-Saharan Africa (SSA) likely due to absence of culturally adapted translations. For this reason, we translated the NIHSS to Swahili in a bid to promote its local use as an initial measure in the standardization of stroke care in the East African region. Swahili remains among the 10 most commonly spoken languages in the world, with over 200 million speakers, mostly centred in East Africa. - METHODS: The NIHSS was translated into Swahili by a team of native Swahili speakers composed of two stroke physicians, two speech therapists and one nurse, and three independent translators in collaboration with the tool's developer. Two Swahili translators performed forward translations of the original document from English to Swahili while a third independent translator performed backward translations to English, which was followed by clinician and cognitive reviews. Afterwards, reviewers from Kenya and Tanzania reviewed the tool for cross-cultural adaptation and international harmonisation. We further reconciled and generated a draft tool that was validated in Kenya and Tanzania. - RESULTS: The NIHSS was translated into Swahili, a process that involved broad modifications of the tool including alterations of images, words and phrases to more locally familiar scenes and items. The results of validation of the Swahili version of the NIHSS in Kenya and Tanzania showed no significant differences with the original tool; with good interrater reliability in most domains. - CONCLUSIONS: The result of this process is a Swahili translation of the NIHSS that reflects the original tool. We expect the tool to help advance stroke care in Swahili-speaking regions.
Gesehen am 20.01.2026